Delay in provision of breast cancer care in patients seen at a district hospital diagnostic breast unit in South Africa - Ng'ang'a, Mukuhi (Department of Surgery, 2018)
Background: There is evidence to show that delays in breast cancer management are detrimental to patient outcome. The aim of this study was to determine time trends and causes of delay in a newly established diagnostic breast clinic based at a district hospital in South Africa. Method: All patients who presented to Mitchells Plain District Hospital Breast Clinic from January to December 2015 and had a diagnosis of breast cancer were included in this study. The intervals between the time she first noted her symptoms to initial contact with a health professional and delivery of definitive therapy was documented. Patient delay referred to the interval from when the patient first noted her symptoms to her initial contact with a health care provider. Provider delay referred to the interval between the first hospital visit and onset of therapy. Result: A total of 33 patients were enrolled in this study. The median overall total delay (time lapse between the moment the patient first noticed her symptoms to time definitive anti-cancer treatment was started) was 157days, (range 29 to 839 days). Median patient delay (time lapse between the moment the patient first noticed her symptoms and the visit to a health professional) was 56 days, (range 7 to 730 days). Median overall provider delay (time lapse between the patients' first encounter with a clinician to time definitive anti-cancer treatment was started) was 84 days, (range 22 to 338 days). Median Referral delay was 11 days (range 4 to 39 days). Median Diagnostic delay was 15 days (range 9 to 135 days) and median treatment delay was 45 days (range 5 to 246 days). Conclusion: The median overall total delay for patients diagnosed with breast cancer at Mitchells Plain District Hospital does not compares well with institutions in developed nations but it is similar to studies done in developing nations. The largest contributor to this delay was patient delay. The main contributors to provider delay was related to diagnosis (almost exclusively related to tissue diagnosis) and treatment (mainly patients who received surgery as their first definitive therapy).